Implementing citizenship education and intercultural competence through stories - Inácio, Carla Isabel Batista Rodrigues (2018)
This research project explored how storytelling contributed to implementing citizenship education and intercultural competence at primary level. Educating children to become clear-thinking and enlightened citizens, as well as to achieve successful interaction with elements of different cultures was the aim of this research. This research project investigated the use of storytelling, using folktales from two distant countries. One of them was Indonesia, a predominantly Islamic country located in the southern hemisphere, and the other Russia, a predominantly Orthodox country located on the European and Asian continents. These stories exposed students to different countries, traditional clothing, landscapes and physical characteristics, but also to customs, rituals and practices of their inhabitants. They were clear facilitators to promote the curiosity of students, to help them notice the differences by contrasting their own reality with the ones of the target cultures. It can be stated that these folktales were valid contributions to raise students’ intercultural awareness. The stories also allowed young learners to be exposed to actions related to moral values, which might be otherwise hard to explain to children. Students connected with the characters of the stories and students’ feelings and emotions helped them learn such concepts, as well as rousing in them emotional and critical engagement. The effectiveness of storytelling was confirmed given that students emerged with new insights and they helped define and introduce concepts to students, as well. Using storytelling was meaningful to make children aware of the positions of others and to engage them as active citizens.